2016
DOI: 10.1186/s13068-016-0603-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomass traits and candidate genes for bioenergy revealed through association genetics in coppiced European Populus nigra (L.)

Abstract: BackgroundSecond generation (2G) bioenergy from lignocellulosic feedstocks has the potential to develop as a sustainable source of renewable energy; however, significant hurdles still remain for large-scale commercialisation. Populus is considered as a promising 2G feedstock and understanding the genetic basis of biomass yield and feedstock quality are a research priority in this model tree species.ResultsWe report the first coppiced biomass study for 714 members of a wide population of European black poplar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 117 publications
3
28
0
Order By: Relevance
“…4c). Despite the relatively larger population size ( n = 732) when compared to populations used in previous GWAS in forest trees (typically between ~300 and ~700 individuals), our results are consistent with the fact that very few associations were also found for growth in all those reported GWAS to date [5259]. Population sizes used have been small, such that experiments have suffered from low power to detect the likely large number of small effect loci controlling growth.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4c). Despite the relatively larger population size ( n = 732) when compared to populations used in previous GWAS in forest trees (typically between ~300 and ~700 individuals), our results are consistent with the fact that very few associations were also found for growth in all those reported GWAS to date [5259]. Population sizes used have been small, such that experiments have suffered from low power to detect the likely large number of small effect loci controlling growth.…”
Section: Discussionsupporting
confidence: 84%
“…Population sizes used have been small, such that experiments have suffered from low power to detect the likely large number of small effect loci controlling growth. Integrating linkage mapping data from bi-parental pedigrees with association populations has been attempted but results have not improved and only a handful of associations have been found, again explaining very little of the genetic variation [56, 57, 59]. Our direct comparison between GS and GWAS is novel and more explicitly corroborates the fact that while genome-wide regression is able to account for large proportions of the pedigree-heritability (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…Various studies attempted GWAS for growth traits in forest trees, namely in Populus (Porth et al ., ; Allwright et al ., ; Du et al ., ; Fahrenkrog et al ., ), Pinus (Bartholomé et al ., ; Lu et al ., ) and Eucalyptus (Cappa et al ., ; Müller et al ., ; Resende et al ., ). Despite the considerably large number of individuals used in our study for each population and for the combined dataset, our results suggested that much larger numbers will be necessary to identify discrete regions capturing larger fractions of the genetic variance of complex traits as indicated by simulations (Spencer et al ., ; Visscher et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have been made in the identification of putative loci underlying phenotypic variation of growth- and development -related traits. These works explored natural genetic variation by means of QTLs [11] genome-wide association studies (GWAS), from populations of Populus species growing in common gardens [12–14], and as SRC [15]. …”
Section: Introductionmentioning
confidence: 99%